On the relationship between effective demand and income distribution in a Kaleckian framework - HALEVI, J. (PSL Quarterly Review, 2014)
The work takes up some issues raised by Kalecki in his posthumously published article “Class struggle and distribution of national income”. By using Marx’s schemes of reproduction, Kalecki was able to prove that, in a given short period, a part of the wage bill is positively related to the level of profits in the consumption goods sector and through the latter, to the level of aggregate profits. Following Kalecki’s methodology of a two sector Marxian model, the author introduces inventories into the framework. In order to do so critical analysis of the supply functions postulated in most of his earlier works on oligopolistic pricing is provided. It is then demonstrated how even under the most favourable short-run technological conditions, bottlenecks may arise depending on the price/cost relation and on the level of inventories in the way described by Hicks. Finally, capital accumulation is introduced into the framework and it is argued that longer run inventories play a much reduced role. JEL: E25, E11, E12, B50